Value-Sensitive Design for Responsible Data Sharing in Governmental Ecosystems - van de Wal, Christel (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Advances in data-sharing technologies offer governments opportunities to improve efficiency and public service delivery. However, ethical risks, legal constraints, and concerns about public trust often limit the adoption of data-sharing practices within governmental organisations. This study examines how Value-Sensitive Design (VSD) and collaboration technologies, including Distributed Ledger Technology (DLT) and Privacy Enhancing Technologies (PETs), can support responsible and trustworthy data sharing in public governance. The research addresses ethical, legal, and organisational tensions while safeguarding public values and fundamental rights. A mixed-method research design combines literature reviews, qualitative case studies, and empirical validation, structured according to design science research principles. Building on analyses of governance frameworks and case studies in Dutch governmental organisations, the study develops and operationalises a methodological and normative framework for responsible data sharing. The research adapts VSD to governmental data ecosystems and provides a structured design approach supporting ethical and privacy-preserving data-sharing practices in public administration.